Switching to Tenofovir Alafenamide, Coformulated With Elvitegravir, Cobicistat, and Emtricitabine, in HIV-Infected Patients With Renal Impairment: 48-Week Results From a Single-Arm, Multicenter, Open-Label Phase 3 Study. (15th April 2016) - Pozniak, Anton; Arribas, Jose R.; Gathe, Joseph; Gupta, Samir K.; Post, Frank A.; Bloch, Mark; Avihingsanon, Anchalee; Crofoot, Gordon; Benson, Paul; Lichtenstein, Kenneth; Ramgopal, Moti; Chetchotisakd, Ploenchan; et al.
Abstract : Background: Tenofovir alafenamide (TAF) is a novel tenofovir prodrug with improved renal and bone safety compared with TDF-containing regimens. We report the 48 week safety and efficacy of a once-daily single tablet regimen of elvitegravir 150 mg (E), cobicistat 150 mg (C), emtricitabine 200 mg (F), and TAF 10 mg (E/C/F/TAF) in HIV-1-infected patients with mild to moderate renal impairment. Methods: We enrolled virologically suppressed HIV-1-infected subjects with estimated creatinine clearance (CrCl) 30–69 mL/min in a single-arm, open-label study to switch regimens to E/C/F/TAF. The primary endpoint was the change from baseline in glomerular filtration rate estimated using various formulae. This study is registered with ClinicalTrials.gov, number NCT01818596. Findings: We enrolled and treated 242 patients with mean age 58 years, 18% Black, 39% hypertension, 14% diabetes. Through week 48, no significant change in estimated CrCl was observed. Two patients (0.8%) discontinued study drug for decreased creatinine clearance, neither had evidence of renal tubulopathy and both had uncontrolled hypertension. Subjects had significant improvements in proteinuria, albuminuria, and tubular proteinuria ( P < 0.001 for all). Hip and spine bone mineral density significantly increased from baseline to week 48 (mean percent change +1.47 and +2.29, respectively, P < 0.05). Ninety-two percent (222 patients) maintained HIV-1 RNA <50 copies per milliliter at week 48. Interpretation: Switch to E/C/F/TAF was associated with minimal change in GFR. Proteinuria, albuminuria and bone mineral density significantly improved. These data support the efficacy and safety of once daily E/C/F/TAF in HIV+ patients with mild or moderate renal impairment without dose adjustment. Abstract : Supplemental Digital Content is Available in the Text.